Cetane Number Improvement of Distilled Diesel from Tawke Wells - Majeed, S. M. N. K.; Idrees, S. A.; Musa, V. A.; Simo, S. M.; Mohammed, A. A.; AbdulKareem, L. A. (Engineering, Technology & Applied Science Research, 2021)
The current research aims to improve the cetane number of diesel extracted from the crude oil of Tawke region-Iraq Kurdistan. A specific mixture of chemical compounds was prepared which included m-nitrophenol, 4-nitro toluene, and nitrobenzene. The components’ effects were investigated with regard to the cetane number, flash point, viscosity, and refractive index of diesel. The quantity of each compound mixed with diesel was prepared based on the statistical analysis of the experiment device (Box–Behnken Designs-BBDs). The tested mixture showed a good agreement and improvement of cetane and flash point and a very low effect on viscosity and refractive index. According to the statistical analysis, the main influence on cetane number and the flashpoint was from m-nitrophenol. The investigation showed that the best results were acquired from the samples of 25PPM 4-nitro toluene and 50PPM m-nitrophenol with a cetane number of 65.3. The correlation and the interaction of the regression equation were linear with all cases. It is worth mentioning that all additives positively influenced the cetane number in the regression equation. The sulfur content was measured as well, and the obtained weight percentage of sulfur was 0.8404%.